Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M.; Morcuende, D.; Ramírez, R.; Ventanas, J.; Cava, R. (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
The following values have no corresponding Zotero field: accession-num: 22061520
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs

Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M; Morcuende, D; Ramírez, R; Ventanas, J; Cava, R (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs